Ethnobotanical survey on plants reputed as aphrodisiacs in Lubumbashi and its surroundings - KABEYA, Justin KANDA; MBUYU, Eddy ILUNGA; MUAMBA, Lambert MALANGU; DIKALA, François OTETE; MUNAKONGO, Daniel EBALANTSHIM; MALOBA , James MWINENSENGE; MBUYI , Serge KALONJI; MBAYO , Marsi KITAMBALA; KANANGILA, Albert BUJITU; KALONDA , Emery MUTOMBO; LUMBU, Jean-Baptiste SIMBI (Orapuh Journal, 2025)
Introduction Despite the scarcity of studies on plant-based aphrodisiacs in this region, this research aims to address the gap by documenting local knowledge. The study sought to identify plants reputed to have aphrodisiac properties in Lubumbashi and its surroundings and to describe their traditional uses. Purpose To conduct an ethnobotanical investigation of plants reputed as aphrodisiacs in Lubumbashi and its surrounding areas. Methods This descriptive ethnobotanical study employed a semi-structured questionnaire administered to 35 key informants. The survey identified 52 plant species reputed to have aphrodisiac properties. The collected data underwent descriptive analysis to determine the most frequently cited species and their modes of use. Results We documented 52 plant species belonging to 31 families, with Fabaceae being the most represented (13.5%). Decoction (62.5%) was the predominant preparation method, and oral administration (74.8%) the most common route. The underground parts of plants were most frequently used (45.9%), particularly roots (40.7%). Among the 35 respondents (54.3% men, mean age ≈ 50 years), sexual weakness (39.4%) and low libido (26.8%) were the most frequently reported conditions treated. Conclusion These findings provide a valuable database on aphrodisiac plants in the region, highlight Fabaceae taxa for phytochemical screening, and support the integration of traditional remedies into sexual health research.